Pathogenic potential of Escherichia coli from various sources in Port Harcourt, Rivers State, Nigeria - K. Otokunefor; P. Nyema (Journal of Applied Sciences and Environmental Management, 2019)
Despite its occurrence as a commensal, Escherichia coli is also notorious as a pathogen. One variation between these commensals and pathogens is the presence of specific factors one of which are the pathogenicity islands. One of the most commonly occurring of these is the PAI IV536. Potentially pathogenic species have been described in nonclinical settings. This often raises concerns on the role these environments play in transmission. This study therefore aimed at comparing the pathogenic ability of E. coli isolates from clinical and non-clinical sources based on the presence of the PAI IV536 marker. Thirty-five E. coli isolates were analyzed in this study. Following DNA extraction by boiling, the PAI IV536 gene fragment was amplified following standard procedure using the F5′-AAGGATTCGCTGTTACCGGAC-3′ and R5′-TCGTCGGGCAGCGTTTCTTCT-3′ primer pair. Of the 35 isolates, 13 were from clinical sources and 22 from nonclinical sources. In total, 25.7% (9/35) of the E. coli isolates in this study were found to possess the PAI IV536 gene. Clinical isolates had a much higher association of 61.5% with the PAI IV536 gene than non-clinical which only had a 4.5% representation of the PAI IV536 gene. This study reports on the detection of PAI IV536 in E. coli isolates from Port Harcourt, Rivers State Nigeria and a lower association of this pathogenicity marker with non-clinical isolates.